1994
DOI: 10.1038/hdy.1994.181
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of dioecy: can nuclear–cytoplasmic interactions select for maleness?

Abstract: A model of evolution of reproductive systems, when sex is determined by both nuclear and cytoplasmic genes, is presented. Such a control of sex is known to facilitate the occurrence of female individuals in hermaphroditic populations, thus leading to gynodioecy. A two-cytotypes two-nuclear loci (two alleles at each nuclear locus) model for gynodioecy has been developed previously. Such gynodioecious systems are usually considered as stable, i.e. not leading to dioecy. In order to find out if the presence of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 24 publications
2
50
0
Order By: Relevance
“…This reproductive system has evolved many times independently in flowering plants (reviewed by Renner and Ricklefs (1995)). Gynodioecy may sometimes be a step in the evolutionary route from hermaphroditism to dioecy (reviewed by Barrett (2002)) and several theoretical studies have shown that nucleo-cytoplasmic gynodioecy (as in S. nutans) can evolve towards dioecy, through the replacement of hermaphrodites by males (Maurice et al, 1994;Schultz, 1994). Although this evolutionary transition has received little empirical support (Spigler and Ashman, 2012), it could have occurred in the genus Silene.…”
Section: Discussionmentioning
confidence: 99%
“…This reproductive system has evolved many times independently in flowering plants (reviewed by Renner and Ricklefs (1995)). Gynodioecy may sometimes be a step in the evolutionary route from hermaphroditism to dioecy (reviewed by Barrett (2002)) and several theoretical studies have shown that nucleo-cytoplasmic gynodioecy (as in S. nutans) can evolve towards dioecy, through the replacement of hermaphrodites by males (Maurice et al, 1994;Schultz, 1994). Although this evolutionary transition has received little empirical support (Spigler and Ashman, 2012), it could have occurred in the genus Silene.…”
Section: Discussionmentioning
confidence: 99%
“…Because the thrum haplotype is dominant over the pin one (Ganders 1979b), restorer genes would not be expressed in thrum plants, producing thrum-biased male sterility. Restorer alleles would only be expressed in pin individuals, and therefore, the costs of restoration (the deleterious pleiotropic effects of the nuclear restorers, Charlesworth 1991;Maurice et al 1994) would only be paid by plants expressing this morph.…”
Section: Discussionmentioning
confidence: 99%
“…Male sterility in gynodioecious species is often determined by the interaction of nuclear and cytoplasmic genes (Saumitou-Laprade et al 1994;Schultz 1994;Manicacci et al 1996; Thompson et al 1998). Theoretical models have shown that dioecy evolves in less restrictive conditions when it originates from nuclear-cytoplasmic gynodioecy than from other forms of genetic determination (Maurice 1992;Maurice et al 1994;Schultz 1994). In fact, gynodioecy could be a common pathway in the evolution of gender specialization in plants because it represents one of the three mutations required for dioecy to evolve (Schultz 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In populations that are polymorphic at both the CMS and nuclear restorer loci, sex is determined by the epistatic interaction between these loci [25,26]. Sex determination can become nuclear if selection sweeps the male sterile cytoplasm to fixation, leaving the nuclear restorer gene polymorphic [27,28]. Thus, fixation of the CMS cytotype and evolution of nuclear sex-determination can also be viewed as a critical prerequisite for the evolution of dioecy.…”
Section: Introductionmentioning
confidence: 99%